Pendidikan Multikultural Antara NU dan Muhammadiyah - Kasman; Makhrus (Journal of Islamic Education Research, 2021)
The emergence of a religious climate that does not reflect of multiculturalism and pluralism lately, which is marked by the strengthening of radical, exclusive, intolerant attitudes and behaviors in responding to others, along with theological racism, raises big questions about the role of pesantren in maintaining religious pluralism. Based on above reality, this research focuses on comparing two Islamic boarding schools, NU and Muhammadiyah, in Jember, related to the construction of multicultural education development, which includes the ideas related to the significance of multicultural education, and the response to the implementation of multicultural education in the education system of NU and Muhammadiyah pesantren. The results of this research, both the Al-Qodiri Islamic Boarding School or the Pakusari Muhammadiyah Islamic Boarding School see the need for multicultural education, but how to apply it, there are differences between them. Although in general the Al-Qodiri Islamic Boarding School and the Modern Muhammadiyah Islamic Boarding School respond well to multicultural education, both have different response to the implementation of multicultural education values.